2006
DOI: 10.1007/s00000-006-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional crystal geometry of binary intermetallic alloys

Abstract: The present work is devoted to a search for general crystal geometry laws of AB and А 3 В binary alloys. Histograms of distribution of the B2, L1 0 , В19, L1 1 , L1 2 , D0 22 , D0 23 , D0 19 , D0 24 , and А15 structures versus the dimensional factor, space filling factor, and superstructure contraction are constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The calculation method and the methodology of the use of these parameters for the analysis of crystalline structures are detailed in [3].…”
Section: Research Resultsmentioning
confidence: 99%
“…The calculation method and the methodology of the use of these parameters for the analysis of crystalline structures are detailed in [3].…”
Section: Research Resultsmentioning
confidence: 99%
“…Earlier, we have shown that alloys of a А 3 В composition with the hexagonal structures (here belongs the D0 24 structure, Fig. 3c) occupy a significant range of the scaling factor values: from 0.8 to 1.4 [15]. The numerical scaling factor values of the intermetallic Ni 3 Ti compound with the D0 24 structure fall practically in the very center of the interval of possible values, which is given in the distribution in Fig.…”
Section: Scaling Factor Role In Forming Phases In the Ni-ti Systemmentioning
confidence: 93%
“…The best examples of D0 22 and D0 23 intermetallics are TiAl 3 and ZrAl 3 , respectively. [ 33 ] It is observed that, in general, all group V trialuminides produce D0 22 crystal structure whereas group III trialuminides create L1 2 crystal structure. [ 34 ] However, the group IV trialuminides are having metastable L1 2 structure and readily transforms into either D0 22 or D0 23 structures.…”
Section: Crystal Structures Of Intermetallic Compoundsmentioning
confidence: 99%